If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 7(2x + 4) = 8(7x + 7) + 1 Reorder the terms: 7(4 + 2x) = 8(7x + 7) + 1 (4 * 7 + 2x * 7) = 8(7x + 7) + 1 (28 + 14x) = 8(7x + 7) + 1 Reorder the terms: 28 + 14x = 8(7 + 7x) + 1 28 + 14x = (7 * 8 + 7x * 8) + 1 28 + 14x = (56 + 56x) + 1 Reorder the terms: 28 + 14x = 56 + 1 + 56x Combine like terms: 56 + 1 = 57 28 + 14x = 57 + 56x Solving 28 + 14x = 57 + 56x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-56x' to each side of the equation. 28 + 14x + -56x = 57 + 56x + -56x Combine like terms: 14x + -56x = -42x 28 + -42x = 57 + 56x + -56x Combine like terms: 56x + -56x = 0 28 + -42x = 57 + 0 28 + -42x = 57 Add '-28' to each side of the equation. 28 + -28 + -42x = 57 + -28 Combine like terms: 28 + -28 = 0 0 + -42x = 57 + -28 -42x = 57 + -28 Combine like terms: 57 + -28 = 29 -42x = 29 Divide each side by '-42'. x = -0.6904761905 Simplifying x = -0.6904761905
| 8+4(z-2)=3z+4 | | (z-3)/6*(z+3) | | 7(5+c)=6(c-3) | | 3x-14=-22 | | 3x-5=3x+3 | | x^2+9x+c=0 | | 8t^2-18t-5=0 | | 2.5y+12=5y | | v-1.3=75.2 | | x^2-7x+c=0 | | -3.36=6+5.12 | | 7+12x=69 | | 24x-32=24x-32 | | (2z/3z-9)-(z+1/2z-6) | | 2(x+3)+6=6x-4(-2+x) | | 5(3c-1)-6=13c+3 | | 2z/3z-9-z+1/2z-6 | | 3x-4x=19 | | (3x+6)/(5)=2x-3 | | 5=3/4(5x-4) | | 5y=15-4x | | 6m+16=4m+9 | | 5+2y-4-2y-4= | | 3z^3-300z=0 | | (6x-4)/(2x) | | p+7=39 | | 3(y-5)=18 | | -2/9(3/1-4/9) | | 9x+-2=1 | | -7a=6 | | 32x-6=25x | | 93-6x=30x+17 |